An Adult Female with Periumbilical Pain and Intractable Vomiting; a Photo quiz - Ramawad, Hamzah Adel; Toloui, Amirmohammad; Viguri, Adelaide (Archives of Academic Emergency Medicine, 2023)
A 25-year-old female with no significant past medical history presented to the emergency room with complaints of worsening, sharp, periumbilical pain for two days, with an intensity of 8 out of 10 based on the visual analogue scale. She complained of fever, nausea, anorexia, and multiple episodes of non-bloody, non-bilious emesis. The patient appeared unwell and diaphoretic. Her vital signs were as follows, blood pressure of 108/66 mmHg, heart rate of 106 beats/minute and body temperature of 39.3°C. Physical examination showed a distended abdomen with localized tenderness and guarding in the periumbilical region. A point-of-care ultrasound (POCUS) of the abdomen did not reveal any free fluid. Laboratory testing, which included electrolytes, complete blood count, and renal and liver function revealed no significant abnormalities. Pregnancy test was negative, and urinalysis was unremarkable. The findings of oral and intravenous contrast-enhanced computed tomography (CT) scan of the abdomen and pelvis are shown in figures 1a and 1b.